Implementation on a new tool tip calibration method for biomedical applications - Woratit Onprasert (2018)
Tool tip calibration is an important procedure in most surgical navigations. Investigations on tool tip calibration have been done by several commercial navigation systems, such as, Medtronics, GE, BrainLAB and Materialize. Some of commercial navigation systems require a specific equipment to calibrate the tool tip. Such method is less flexible when performs with different tools. This paper proposes a new method to perform the tool tip calibration which requires the user to point the device's tool tip on a single pivot point for a set of motions. Optical tracking marker is employed by attaching it on the upper part of device to be calibrated. Position and orientation of the marker is calculated by capturing the motions of the marker rotated about the pivot point. The tool tip vector is computed and generated by our developed algorithm based on the concept of reversing the mean of homogeneous transforms or SE(3). The experimental results have shown that collecting only 5 poses of the tool is the optimum point in term of computational time and accuracy for the algorithm. © 2012 Springer-Verlag Berlin Heidelberg.